(6u-7v)(6u+7v)=

Simple and best practice solution for (6u-7v)(6u+7v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6u-7v)(6u+7v)= equation:


Simplifying
(6u + -7v)(6u + 7v) = 0

Multiply (6u + -7v) * (6u + 7v)
(6u * (6u + 7v) + -7v * (6u + 7v)) = 0
((6u * 6u + 7v * 6u) + -7v * (6u + 7v)) = 0

Reorder the terms:
((42uv + 36u2) + -7v * (6u + 7v)) = 0
((42uv + 36u2) + -7v * (6u + 7v)) = 0
(42uv + 36u2 + (6u * -7v + 7v * -7v)) = 0
(42uv + 36u2 + (-42uv + -49v2)) = 0

Reorder the terms:
(42uv + -42uv + 36u2 + -49v2) = 0

Combine like terms: 42uv + -42uv = 0
(0 + 36u2 + -49v2) = 0
(36u2 + -49v2) = 0

Solving
36u2 + -49v2 = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '49v2' to each side of the equation.
36u2 + -49v2 + 49v2 = 0 + 49v2

Combine like terms: -49v2 + 49v2 = 0
36u2 + 0 = 0 + 49v2
36u2 = 0 + 49v2
Remove the zero:
36u2 = 49v2

Divide each side by '36'.
u2 = 1.361111111v2

Simplifying
u2 = 1.361111111v2

Take the square root of each side:
u = {-1.166666667v, 1.166666667v}

See similar equations:

| 8x-3=3-2(4x-3) | | 6y-10-3y+6=0 | | 9+4q=11+3q | | (-3u/v^3)^2 | | (2-a)(5z-7)=0 | | x/3-4=x-7 | | -4a+2=4a+82 | | e/-6=4 | | -7x+10=-3x+22 | | (72-x)=180 | | 5[7-5(-2x-9)]=50x+260 | | 6-2z=2z-10 | | (4x+32)=180 | | 20-1/10d=16 | | 5y+140=7x | | 22.27/x=4.16 | | 3x+2x^2-8x+6x^2= | | 22.27*x=4.16 | | x+22=34 | | 15=2x+10 | | x+22=33 | | 22.27*x=22.27 | | -2e^3x+19=3 | | 5y=7x-140 | | -x^2+6x=-1 | | 154/22 | | 11-3h+9=-8 | | 4x+1=2x+29 | | 3x-4=5x+9 | | https://www.mhcitts.com/images/test/53_1_8s.jpg | | 3x-7=6x-2 | | 165x+2771=7721 |

Equations solver categories